Wilhelm Dilthey’s hermeneutics: identity and biography as construction (in German) - Chetkowsky, Andreas (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2024)
Writing one’s own life story on the basis of one’s memories has the risk of falsification due to unreliable memory. Memory plays a decisive role in Wilhelm Dilthey’s hermeneutic concept and his idea of life history as a whole. For Wilhelm Dilthey, the autobiographical genre is best suited to applying his method of understanding in the humanities. In the context of the subjectivity discourse of the 1970s and psychoanalytical findings, many writers had doubts about the truthfulness of a hermeneutic representation of remembered life. Using the example of Elias Canetti’s autobiographical writing, it is shown that, despite psychoanalytic theories, he follows the hermeneutic approach by adhering to Dilthey´s life-historical-biographical concept of wholeness. His conviction of an unbroken memory enables him to express his identity as an author in his autobiography.
Keywords: hermeneutic; autobiography; humanities; coherence of life; memories